Refined criteria for p53 expression in ovarian mucinous tumours are highly concordant with TP53 mutation status, but p53 expression/TP53 status lack prognostic significance - Dundr, Pavel; Hájková, Nikola; Kendall Bártů, Michaela; Cibula, David; Drozenová, Jana; Fabian, Pavel; Fadare, Oluwole; Frühauf, Filip; Hausnerová, Jitka; Hojný, Jan; Laco, Jan; Lax, Sigurd F; et al. (Pathology, 2023)
In gynecological neoplasms, immunohistochemical (IHC) expression of p53 is generally an accurate predictor of TP53 mutation status if correctly interpreted by the pathologist. However, the literature concerning cut-offs, frequency and prognostic significance of p53 staining in ovarian mucinous tumours is limited and heterogeneous. We performed an analysis of 123 primary ovarian mucinous tumours including mucinous borderline tumours (MBT), mucinous carcinomas (MC), and tumours with equivocal features between MBT and MC. We assessed p53 expression for the three recognised patterns of aberrant staining in ovarian carcinoma [overexpression ('all'), null and cytoplasmic] but using a recently suggested cut-off for aberrant overexpression in ovarian mucinous tumours (strong nuclear p53 staining in ≥12 consecutive tumour cells) and correlated the results with next generation sequencing (NGS) in all qualitatively sufficient cases (92/123). Aberrant p53 expression was present in 25/75 (33.3%) MBT, 23/33 (69.7%) MC (75% of MC with expansile invasion and 61.5% with infiltrative invasion), and 10/15 (66.7%) tumours equivocal between MBT and MC. Regarding the 92 tumours with paired IHC and mutation results, 86 showed concordant results and six cases were discordant. Three discordant MBT cases showed aberrant expression but were TP53 wild-type on sequencing. Three cases had normal p53 expression but contained a TP53 mutation. Overall, IHC predicted the TP53 mutation status with high sensitivity (94.1%) and specificity (92.7%). The accuracy of IHC was 93.5% with a positive predictive value of 94.1% and a negative predictive value of 92.7%. When comparing MC cases with wild-type TP53 versus those with TP53 mutation, there were no significant differences concerning disease-free survival, local recurrence-free survival, or metastases-free survival (p>0.05). In the MBT subgroup, there were no events for survival analyses. In conclusion, using an independent large sample set of ovarian mucinous tumours, the results of our study confirm that the suggested refined cut-off of strong nuclear p53 staining in ≥12 consecutive tumour cells reflect high accuracy, sensitivity and specificity for an underlying TP53 mutation but the TP53 mutation status has no prognostic significance in either MC or MBT.
Keywords: nádorový supresorový protein p53; TP53; ovary; Prognosis; mucinózní adenokarcinom; imunohistochemie; mutace; next generation sequencing; Tumor Suppressor Protein p53; nádory vaječníků; p53; Immunohistochemistry; immunohistochemistry; ženské pohlaví; prognóza; Mutation; Humans; Adenocarcinoma, Mucinous; Female; Ovarian Neoplasms; Mucinous tumours; lidé